The Displacement Risks and Impacts of Hong Kong's Nonindigenous Villagers: A Grounded Theory Analysis. Issue 6 (November 2019) - Castro Campos, Bente; Liao, Kuei-Hsien; Yiu, Edward Chung Yim
Land resumption in Hong Kong, which involves involuntary displacement in contemporary development projects, deliberately targets nonindigenous villages, where many residents are landless farmers. In this article, we examine the risks and impacts associated with such displacement of the nonindigenous villagers through a grounded theory approach. Interviews were conducted with nonindigenous villagers who were either in a pre- or in a post-relocation state as well as with activists who condemn the current development projects in Hong Kong. Our major findings are that displacement risks and impacts of the nonindigenous villagers can be understood against the background of five interrelated factors: marginalization by nonindigenous status, demographic characteristics, economic impacts, mental health, and community attachment. Displacement loss unfolds particularly strong for the landless, often elderly, farmers. While Hong Kong is a highly developed area, its nonindigenous villagers largely face the negative outcomes of development projects, similar to the landless people in the developing world.